Yersinia enterocolitica: Epidemiological Studies and Outbreaks. (16th October 2011) - Rahman, Atiqur; Bonny, Tania S.; Stonsaovapak, Siriporn; Ananchaipattana, Chiraporn
Abstract : Yersinia enterocolitica is the most common bacteriological cause of gastrointestinal disease in many developed and developing countries. Although contaminated food is the main source of human infection due to Y. enterocolitica, animal reservoir and contaminated environment are also considered as other possible infection sources for human in epidemiological studies. Molecular based epidemiological studies are found to be more efficient in investigating the occurrence of human pathogenic Y. enterocolitica in natural samples, in addition to conventional culture based studies.